Characterization of NGFFYamide Signaling in Starfish Reveals Roles in Regulation of Feeding Behavior and Locomotory Systems - Tinoco, Ana B.; Semmens, Dean C.; Patching, Emma C.; Gunner, Elizabeth F.; Egertová, Michaela; Elphick, Maurice R. (Frontiers in Endocrinology, 2018)
Neuropeptides in deuterostomian invertebrates that have an Asn-Gly motif (NG peptides) have been identified as orthologs of vertebrate neuropeptide-S (NPS)-type peptides and protostomian crustacean cardioactive peptide (CCAP)-type peptides. To obtain new insights into the physiological roles of NG peptides in deuterostomian invertebrates, here we have characterised the NG peptide signalling system in an echinoderm – the starfish Asterias rubens. The neuropeptide NGFFYamide was identified as the ligand for an A. rubens NPS/CCAP-type receptor, providing further confirmation that NG peptides are orthologs of NPS/CCAP-type neuropeptides. Using mRNA in situ hybridisation, cells expressing the NGFFYamide precursor transcript were revealed in the radial nerve cords, circumoral nerve ring, coelomic epithelium, apical muscle, body wall, stomach and tube feet of A. rubens, indicating that NGFFYamide may have a variety of physiological roles in starfish. One of the most remarkable aspects of starfish biology is their feeding behaviour, where the stomach is everted out of the mouth over the soft tissue of prey. Previously, we reported that NGFFYamide triggers retraction of the everted stomach in A. rubens and here we show that in vivo injection of NGFFYamide causes a significant delay in the onset of feeding on prey. To investigate roles in regulating other aspects of starfish physiology, we examined the in vitro effects of NGFFYamide and found that it causes relaxation of acetylcholine-contracted apical muscle preparations and induction of tonic and phasic contraction of tube feet. Furthermore, analysis of the effects of in vivo injection of NGFFYamide on starfish locomotor activity revealed that it causes a significant reduction in mean velocity and distance travelled. Interestingly, experimental studies on mammals have revealed that NPS is an anxiolytic that suppresses appetite and induces hyperactivity in mammals. Our characterisation of the actions of NGFFYamide in starfish indicates that NPS/NG peptide/CCAP-type signalling is an evolutionarily ancient regulator of feeding and locomotion.